In-situ X-ray radiography of primary Fe-rich intermetallic compound formation. (1st September 2020) - Feng, Shikang; Liotti, Enzo; Lui, Andrew; Wilson, Matthew D.; Connolley, Thomas; Mathiesen, Ragnvald H.; Grant, Patrick S.
Graphical abstract: Abstract: The formation of primary Fe-rich intermetallic compound crystals and the effect of TiB2 and TiC inoculation during solidification of a hypereutectic Al-Fe alloy has been investigated. Both horizontal, near isothermal conditions and vertical, directional thermal gradient conditions were studied using laboratory and synchrotron X-ray radiography. TiB2 and TiC inoculation enhanced formation of Fe-rich intermetallics under all experimental conditions. Near isothermal solidification resulted in the highest intermetallic number density and average formation rate, whilst increasing the thermal gradient reduced both. A model for intermetallic crystal formation is proposed to explain the effect of thermal gradient and cooling rate on the intermetallic number density and average formation rate.